2021
DOI: 10.3389/fnhum.2021.644892
|View full text |Cite
|
Sign up to set email alerts
|

Global Signal Topography of the Human Brain: A Novel Framework of Functional Connectivity for Psychological and Pathological Investigations

Abstract: The global signal (GS), which was once regarded as a nuisance of functional magnetic resonance imaging, has been proven to convey valuable neural information. This raised the following question: what is a GS represented in local brain regions? In order to answer this question, the GS topography was developed to measure the correlation between global and local signals. It was observed that the GS topography has an intrinsic structure characterized by higher GS correlation in sensory cortices and lower GS correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Furthermore, various studies show that GS is represented reliably in different degrees in different regions, i.e., it displays a dynamic topography (Fig. 1) 10,17,[19][20][21][22][41][42][43][44] (see Box 1 for different ways of calculating the spatial pattern, in terms of GS topography). The potential behavioral and cognitive relevance of GS topography is supported by the observation of topographical changes in various neurologic and psychiatric disorders as these show major alterations in perception and cognition (see below for details).…”
mentioning
confidence: 99%
“…Furthermore, various studies show that GS is represented reliably in different degrees in different regions, i.e., it displays a dynamic topography (Fig. 1) 10,17,[19][20][21][22][41][42][43][44] (see Box 1 for different ways of calculating the spatial pattern, in terms of GS topography). The potential behavioral and cognitive relevance of GS topography is supported by the observation of topographical changes in various neurologic and psychiatric disorders as these show major alterations in perception and cognition (see below for details).…”
mentioning
confidence: 99%
“…Although early studies have found prominent artifacts (i.e. head motion, respiration) in the GS 5 , 6 , numerous recent studies have tied GS fluctuations to vigilance 7 , behavioral traits 8 , brain states 9 , and mental disorders 3 , 10 , suggesting that the GS conveys particular physiological, psychological, and pathological information 11 . A recent study found a close relationship between the GS of rs-fMRI and the global EEG signal at multiple frequency bands 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, significant research studies were carried out to develop GST to analyze the correlation between local and global signals in the rs-fMRI study. It has been observed that the lower GST correlates with different cortical locations, such as the higher-order cortices and sensory cortex (Ao et al, 2021 ). Moreover, GST can be modulated by individual factors, like conscious state and attention-demanding tasks (Ao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the lower GST correlates with different cortical locations, such as the higher-order cortices and sensory cortex (Ao et al, 2021 ). Moreover, GST can be modulated by individual factors, like conscious state and attention-demanding tasks (Ao et al, 2021 ). In addition, abnormal GST has been detected in patients with bipolar disorder, schizophrenia, epilepsy, and major depressive disorder (Li et al, 2019 , 2021 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%